Synoviocyte–chondrocyte triculture model for early-stage PTOA: fibronectin fragment-induced catabolic effects in vitro and in vivo - Khan, Shahid; Cho, Hongsik; Hasty, Karen A.; Brown, Taylor; Bhogoju, Sarayu; Subramanian, Anuradha (Frontiers in Bioengineering and Biotechnology, 2025)
Post-traumatic osteoarthritis (PTOA), a subtype of osteoarthritis initiated by joint trauma, is driven by unresolved early inflammation that ultimately leads to cartilage degeneration. Although animal models have advanced our understanding of disease progression, they offer limited resolution of the early molecular events following trauma. In this study, we developed a transwell-based in vitro triculture model mimicking the early joint environment post-injury, incorporating macrophages, fibroblast-like synoviocytes (FLSs), and human articular chondrocytes (HACs). In lieu of the commonly used macrophage activator, lipopolysaccharide (LPS), this study utilizes fibronectin fragments (Fnfs), which belong to the damage-associated molecules released upon trauma to cartilage, to activate macrophages and simulate post-traumatic inflammation. The triculture was maintained for 12 days while promoting paracrine-only communication between the cell types. The activation of macrophages by Fnfs led to a sustained expression of pNFκB in both HACs and FLSs, as shown by immunofluorescence, alongside increased gene expression of inflammatory mediators MMP3, MMP13, and TNF-α. Fnfs triggered catabolic signaling across all joint-resident cell types used in this model. To support the translational relevance of the in vitro findings, a complementary in vivo experiment in which Fnfs were injected intra-articularly showed increased MMP activity gene expression and reduced COL2A1 gene expression in joint cartilage. The cytokine and gene expression profiles observed in the triculture model closely mirrored those observed in early-stage in vivo PTOA models and in the patient-derived synovial fluid obtained in the early traumatic phase, underscoring the model’s physiological relevance. This triculture platform captures the key aspects of early PTOA processes driven by macrophage activation and offers a biologically relevant tool for mechanistic studies and therapeutic screening.